Occurrence of Monosporascus cannonballus in Watermelon Fields in Tunisia and Factors Associated with Ascospore Density in Soil - Boughalleb, Naima; Salem, Ibtissem Ben; Beltran, Roberto; Vicent, Antonio; Perez Sierra, Ana; Abad-Campos, Paloma; García-Jiménez, José; Armengol, Josep (2017)
Surveys of 11 watermelon fields throughout production areas of this crop in southern and central regions in Tunisia were conducted in 2007 to determine the aetiology and distribution of watermelon vine decline. Monosporascus cannonballus was isolated from diseased roots in all surveyed fields. All the isolates were identified according to morphological features and confirmed by amplification of a fragment of the ITS region with specific primers. Ascospores of M. cannonballus were recovered from soil in all watermelon fields surveyed and the average population densities ranged from 3.65 to 10.14 ascospores per g of soil. Multiple linear regression analysis revealed that only four of the crop and soil factors evaluated had a significant correlation with ascospore density at the end of the growing season: vertisol vs. other soils, disease incidence, percentage of clay and pH. The pH of the soil showed a strong significant negative linear relationship with ascospore density, while the other three factors correlated positively.